Synthesis of a novel analogue of DPP-4 inhibitor Alogliptin: Introduction of a spirocyclic moiety on the piperidine ring - Kodimuthali, Arumugam; Prasunamba, Padala Lakshmi; Pal, Manojit (Beilstein Journal of Organic Chemistry, 2010)
We report the synthesis of a novel analogue of Alogliptin via condensation of two key intermediates one of which is an aminopiperidine derivative bearing a spirocyclic ring on the piperidine moiety. Preparation of the aminopiperidine intermediate was carried out by constructing the cyclopropyl ring prior to assembling the piperidine ring.
Keywords: Alogliptin; cyclopropyl ring; DPP-4; piperidine